Employing virtualization in library computing: use cases and lessons learned. - Hutt A; Stuart M; Suchy D; Westbrook BD (Information Technology & Libraries, 2009)
This paper provides a broad overview of virtualization technology and describes several examples of its use at the University of California, San Diego Libraries. Libraries can leverage virtualization to address many long-standing library computing challenges, but careful planning is needed to determine if this technology is the right solution for a specific need. This paper outlines both technical and usability considerations, and concludes with a discussion of potential enterprise impacts on the library infrastructure.